2017
DOI: 10.1177/0018726717741355
|View full text |Cite
|
Sign up to set email alerts
|

Creative work and affect: Social, political and fantasmatic dynamics in the labour of musicians

Abstract: How can we understand contradictory identifications within work to which one is passionately attached? This article explores how seemingly competing accounts of the self at work can not only appear side by side within the self-presentation of creative workers, but also how dominant patterns within the daily socio-economic realities of creative work are reproduced through faux-contestations of them. Following Glynos and Howarth, I will argue that such transgressive notions often recall earlier historical arrang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…Gaining insight into the ‘intensities’ and ‘forces’ of organizational life requires embodied, corporeal methods that focus on events ‘from which sensible experience emerges’ (Beyes & Steyaert, 2012, p. 52; see also Hoedemaekers, 2017). Fieldwork was therefore oriented towards the lived and felt experiences of workers as they engaged with other matter.…”
Section: A Methodology Of Encounters: Engaging With Mattermentioning
confidence: 99%
“…Gaining insight into the ‘intensities’ and ‘forces’ of organizational life requires embodied, corporeal methods that focus on events ‘from which sensible experience emerges’ (Beyes & Steyaert, 2012, p. 52; see also Hoedemaekers, 2017). Fieldwork was therefore oriented towards the lived and felt experiences of workers as they engaged with other matter.…”
Section: A Methodology Of Encounters: Engaging With Mattermentioning
confidence: 99%
“…In Brodsky’s (2006) interview study with orchestral players, they viewed their career as the essential means to being able to socialize with like-minded others, experience camaraderie, solidarity, and friendship. Using a case study, Hoedemaekers (2018) discovered musicians are concerned with employability and invest efforts into developing social networks to support their career. Indeed, other interview studies also highlight the importance of social networks for managing life as a musician (Coulson, 2012; Dobson, 2011; Lim, 2014; Portman-Smith & Harwood, 2015; Umney & Kretsos, 2014; Vaag et al, 2014).…”
Section: Social Support As a Stress-buffering Resourcementioning
confidence: 99%
“…However, research on the impact of employment characteristics is more recent. Although qualitative studies with musicians have revealed themes related to career insecurity (Coulson, 2012; Cooper & Wills, 1989; Dobson, 2011; Hoedemaekers, 2018; Kirschbaum, 2007; Umney & Kretsos, 2014; 2015; Oakland, MacDonald, & Flowers, 2012; Portman-Smith & Harwood, 2015; Vaag, Giaever, & Bjerkeset, 2014), this is yet to be studied systematically. As such, our research investigates the impact of career insecurity (i.e., a stressor) on a range of potential strains relevant to musicians.…”
mentioning
confidence: 99%
“…Criticism is a response that is usually in the form of evaluation accompanied by a description and excellent and lousy consideration. Most musicians give social criticism against something global or social community [3]. Social criticism can be conveyed through the lyrics poured into a song where the lyrics contain criticism; it can be anything such as about the government or satire to individuals to individuals.…”
Section: Introductionmentioning
confidence: 99%